Prototipe Sistem Keamanan Kas Baterai dan Kendali Lampu pada Rumpon dengan Kendali Telegram - Amien, M.Mifthahul; Jahja, Mohamad; Yunginger, Raghel; Yunus, Muhammad; Tansa , Salmawaty; Nasibu, Iskandar Zulkarnain (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
Fishermen use fishing aids called FADs to take advantage of Indonesia's marine potential. The problem fishermen face using FADs is the frequent loss of essential components in FADs, such as lights, batteries, and solar panels. Previously there was a security system that used SMS and GPS. However, there is no trigger, and still using SMS is a weakness of this existing system. This study aims to help solve this problem by developing a prototype that functions as a security system that no longer uses SMS and has a trigger. Rubot32 is the result of the design of this security system. It has an internal GPS to determine the device's position with sufficient accuracy. This ultrasonic sensor-based trigger will trigger a warning notification on the Telegram Bot and activates a high-voltage stinger and a functioning control system via Telegram Bot.